2006
DOI: 10.1097/01.prs.0000185867.84172.c0
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Zones of the DIEP Flap Revisited: A Clinical Study

Abstract: On the basis of the results of this study, the Hartrampf concept of a centrally perfused skin ellipse with declining perfusion of its peripheral ends is wrong and should be revised. Instead, one should think of the lower abdominal flap as two halves separated by the midline. The ipsilateral half has an axial pattern of perfusion; the contralateral half shows a random-pattern, individually variable blood supply. Therefore, the classic Hartrampf zones should be rearranged, switching zones II and III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
149
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(155 citation statements)
references
References 18 publications
1
149
1
4
Order By: Relevance
“…From this experience, we concluded, like others, that the original TRAM flap zone 1 to 4 classification does not hold up. 12 There seems to be a midline venous "divide," which regularly limits a substantial part of zone 2 to be used. This finding does not support earlier reported routine unproblematic use of all zones of an entire DIEP flap on 1 or more perforators in one zone.…”
Section: Discussionmentioning
confidence: 99%
“…From this experience, we concluded, like others, that the original TRAM flap zone 1 to 4 classification does not hold up. 12 There seems to be a midline venous "divide," which regularly limits a substantial part of zone 2 to be used. This finding does not support earlier reported routine unproblematic use of all zones of an entire DIEP flap on 1 or more perforators in one zone.…”
Section: Discussionmentioning
confidence: 99%
“…12 Holm et al challenged the Hartrampf perfusion zones and suggested that perfusion in a DIEP flap travels first to the ipsilateral side before crossing the midline. 13 1 and 2). The group did not notice a difference in the occurrence of fat necrosis within hemiflaps based solely on the medial versus the lateral row.…”
Section: A C C E P T E Dmentioning
confidence: 95%
“…Many endogenous substances, such as elastin, collagen, keratin, NAD(P)H and FAD, tryptophan and flavins, give rise to what is referred to as autofluorescence [4]. The diagnostic capability can be enhanced by exogenous contrast agents, such as aminolaevulinic acid (ALA)-induced protoporphyrin IX (PpIX) [5] and indocyanine green (ICG) [6]. The use of ultraviolet (UV) or near-UV excitation light efficiently excites many endogenous and exogenous fluorophores but also limits the depth of sensitivity to the uppermost hundred micrometres due to the strong attenuation by substances, such as haemoglobin or melanin, at these short wavelengths.…”
Section: Article In Pressmentioning
confidence: 98%
“…Exogenous contrast agents have also found use in diagnosis of non-malignant indications, such as fluorescein [22] and ICG [23] angiography for the detection of retinal disorders as well as ICG angiography for use during skin flap surgery [6].…”
Section: Article In Pressmentioning
confidence: 99%